An 18th-Century Prose Story: Câlibü’s-Sürûr ve Dâfi'u’l-Gumûm - Yasemin Karakuş (İstanbul Üniversitesi Edebiyat Fakültesi Türk Dili ve Edebiyatı Dergisi)
Classical Turkish literature progressed from the two primary branches of verse and prose in a tradition that has continued for centuries. Many prose stories have been written within the framework of Ottoman literature and narrative tradition based on story-related narratives covering a variety of topics such as love, heroism, morality, religion, and mysticism. Câlibü's-sürûr ve Dâfièu'l-Gumûm was written at the beginning of the 18th century by an unknown author and is an example of a prose work. It is cataloged under number T1854 in the Turkish Manuscripts Division of the Rare Books Library of Istanbul University. This work describes the endless struggles between drunkards and opium addicts and was presented to Nikolas Mavrocordatos, the hospodar [Governor of Wallachia and Moldavia under the Ottoman Porte] of the period for his young son’s entertainment. The story was written with a simple language and humorous style and draws attention through its background to the harmful effects of pleasure-indulging substances on human health, with the main aim being to teach the style of works on history and war through the stereotypical expressions used in the work. This study will introduce the versatile work titled Câlibü's-sürûr ve Dâfièu'lGumûm and draw attention to its distinctive features.